Teaching Profession in Technical Education in Community Schools - Ghaju, Bikash; Bhattarai, Prakash C. (Journal of Training and Development, 2021)
Technical Education in Community School (TECS) is considered pertinent for the socio-economic transformation, particularly in a developing country like Nepal. Instructors of these schools are the key persons who transform curriculum into practice, however, their profession in their perspectives was hardly studied. With this consideration, this study was carried out to understand the experience of TECS instructors on their teaching profession. To attain this research objective, four instructors from the Diploma in Civil Engineering program of two TECSs were purposively selected, and a narrative inquiry approach was utilized to study the cases in-depth. The result showed that the instructors were interested in teaching in TECS; however, they were not ready to go to TECSs of remote villages. For them, the village settings lacked source for extra earning opportunities and career growth prospects. They were motivated to teach in Diploma in Civil Engineering as they could apply their prior knowledge and skills. At the same time, theoretical knowledge gained from their teaching in TECSs had been helpful for their engineering profession as well.